Xc− inhibitor sulfasalazine sensitizes colorectal cancer to cisplatin by a GSH-dependent mechanism. Issue 1 (1st November 2015) - Ma, Ming-zhe; Chen, Gang; Wang, Peng; Lu, Wen-hua; Zhu, Chao-feng; Song, Ming; Yang, Jing; Wen, Shijun; Xu, Rui-hua; Hu, Yumin; Huang, Peng
Highlights: xCT is highly expressed in CRC. SSZ promotes substantial accumulation of ROS in CRC. SSZ and CDDP cause more than additive ROS accumulation in CRC. SSZ and CDDP cause synergistic cytotoxic effect in CRC cells. SSZ enhances cellular platinum level and DNA damage induced by CDDP. Abstract: Sulfasalazine (SSZ) is an anti-inflammatory drug that has been demonstrated to induce apoptosis and tumor regression through inhibition of plasma membrane cystine transporter xc − . Cysteine is a rate-limiting precursor for intracellular glutathione (GSH) synthesis, which is vital for compound detoxification and maintaining redox balance. Platinum-based chemotherapy is an important regimen used in clinics for various cancers including colorectal cancer (CRC). We hypothesized that targeting xc − transporter by SSZ may annihilate cellular detoxification through interruption of GSH synthesis and may enhance the anti-cancer activity of cisplatin (CDDP) by increasing drug transport. In the present study, we revealed that xCT, the active subunit of xc −, is highly expressed in CRC cell lines and human colorectal carcinoma tissues compared with their normal counterparts. SSZ effectively depleted cellular GSH, leading to significant accumulation of reactive oxygen species and growth inhibition in CRC cells. In contrast, the normal epithelial cells of colon origin were less sensitive to SSZ, showing a moderate ROS elevation. Importantly, SSZ effectively enhanced the intracellular platinum level and cytotoxicity of CDDP in CRC cells. The synergistic effect of SSZ and CDDP was reversed by antioxidant N-acetyl-L-cysteine (NAC). Together, these results suggest that SSZ, a relatively non-toxic drug that targets cystine transporter, may, in combination with CDDP, have effective therapy for colorectal cancer.